2004
DOI: 10.1002/cjoc.20040221122
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the interaction between rutin and DNA in the absence and presence of β‐cyclodextrin by electrochemical and spectroscopic methods

Abstract: bThe interactions between rutin or the inclusion complex of rutin-Fcyclodextrin and DNA were investigated by means of cyclic voltammetry, W-vis absorption spectroscopy and fluorescence emission spec~oscopy. The apparent binding constant of rutin with DNA is found to be 2.9X lo4 LJmol. The results showed that the benzopyranic-4-one plane of rutin mainly intercalated into DNA in the absence of pcyclodextrin, while the catecholic portion of rutin was located in the double helix of DNA in the presence of pcyclodex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…For small molecules binding to active sites on a macromolecule, the formation or binding constant can be estimated from the expression in Eq. (1) [28][29][30][31][32][33].…”
Section: Estimation Of Formation Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…For small molecules binding to active sites on a macromolecule, the formation or binding constant can be estimated from the expression in Eq. (1) [28][29][30][31][32][33].…”
Section: Estimation Of Formation Constantsmentioning
confidence: 99%
“…The straight trend obtained is the typical Benesi-Hildebrand plot for the estimation of the formation constant of molecular complexes [28][29][30][31][32][33]. From the plot of A 0 /(A − A 0 ) against 1/[DNA], the ratio of the intercept to the slope gives the formation constant, K f .…”
Section: Estimation Of Formation Constantsmentioning
confidence: 99%
“…6B shows that the peak position of 30 lM 2 is shifted bathochromically from k max = 396 to 403 nm by the addition of 80 lM DNA, accompanied with hypochromic shift from 0.796 to 0.307. These remarkable spectral characteristics suggest intercalation of 2 into the stacked base pairs domain of DNA [31][32][33]. The hypochromic effect is caused by the overlapping of the electronic states of the intercalating chromophore of the complex 2 with the DNA bases [34] and the bathochromic shift is caused by the lowering in pp * transition energy of the complex due to its ordered stacking between the DNA base pairs after intercalation [35].…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
“…The interactions between rutin or the inclusion complex of rutin--cyclodextrin and DNA were investigated by cyclic voltammetry [65]. The results showed that the benzopyranic-4-one plane of rutin mainly intercalated into DNA in the absence of -cyclodextrin, while the catecholic portion of rutin was located in the double helix of DNA in the presence of -cyclodextrin.…”
Section: Electrochemicalmentioning
confidence: 99%